2017
DOI: 10.15448/1984-7726.2017.1.25419
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da língua, estilo de elocução e sexo do falante sobre medidas globais da frequência fundamental

Abstract: Este artigo está licenciado sob forma de uma licença Creative Commons Atribuição 4.0 Internacional, que permite uso irrestrito, distribuição e reprodução em qualquer meio, desde que a publicação original seja corretamente citada. http://creativecommons.org/licenses/by/4.0/deed.pt_BR http://dx.doi. org/10.15448/1984-7726.2017.1.25419 Efeito da língua, estilo de elocução e sexo do falante sobre medidas globais da frequência fundamental 1 Resumo: Analisamos o efeito do sexo, do estilo de elocução e da língua (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Research on speaking styles stems from a general scientific interest in discovering the effects of non-structural linguistic factors on the process of speech production. There is a growing body of research on the subject, a representative sample of which is presented in review papers (see [1,2] and references therein). Knowledge about this subject, nonetheless, can be brought to bear on more applied endeavors, such as in the field of forensic phonetics research and practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on speaking styles stems from a general scientific interest in discovering the effects of non-structural linguistic factors on the process of speech production. There is a growing body of research on the subject, a representative sample of which is presented in review papers (see [1,2] and references therein). Knowledge about this subject, nonetheless, can be brought to bear on more applied endeavors, such as in the field of forensic phonetics research and practice.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work, we analyzed this same corpus in search for effects of language, speaking style and speaker sex on global measures of fundamental frequency [2]. There we focused on measures of central tendency and variability of f0 and a number of statistically significant effects were uncovered.…”
Section: Introductionmentioning
confidence: 99%
“…This may be explained by the significantly greater variation in spontaneous speech. Standard deviation in semitones for the full data set are 2.6 st for the spontaneous versus 2.2 st for the other styles as measured in a study using the same corpus [7]. If the languages are analysed separately, the same pattern appears, SD is systematically greater in spontaneous speech.…”
Section: Discussionmentioning
confidence: 74%
“…In another recent study [7] that looked into the effect of language, speaking style and speaker sex on a number of statistical measures of f0, the base value and the median deviation from the base value were found to be fairly robust against the influence of these factors.…”
Section: Introductionmentioning
confidence: 93%
“…At the start, we stated that one of the goals in this article is to bring together the two lines of research we described. This is done by reanalyzing a speech corpus that has already been studied by Arantes and Linhares (2017) with the purpose of finding evidence for the effect of speaking style on f0. In that study, the authors found the effects by looking at differences in a set of measures of central tendency and variability of f0.…”
Section: Introductionmentioning
confidence: 99%